THE EFFECT OF NUTRITION EDUCATION BASED ON HALAL FOOD THROUGH MOTION GRAPHIC ANIMATION AUDIOVISUAL MEDIA ON THE KNOWLEDGE AND ATTITUDES OF ADOLESCENTS - Mufidah, Indahtul; Ajeng, Oktavia Bela Dyah A; Pibriyanti, Kartika; Damayanti, Amilia Yuni (Darussalam Nutrition Journal, 2024)
Background: Indonesian adolescents face a triple burden of malnutrition, namely undernutrition, obesity and micronutrient deficiencies. Knowledge and attitude play an important role in overcoming nutrition problems. Increasing nutrition awareness, especially those based on halal food, can be done through nutrition education from an early age. Motion graphic animation video is one of the effective learning media with attractive visual advantages and increases learning enthusiasm. Objective: This study aims to determine the effect of halal food-based nutrition education through animated audiovisual media on adolescents' knowledge and attitudes related to nutrition. Method: The study used Quasy Experimental Pre-test and Post-test group design. The sample was divided into experimental and control groups, with a pre-test, intervention, and post-test process. The sampling technique used purposive sampling. The research sample consisted of two groups with a total of 112 people, in each group there were 56 people. The variables measured involved adolescents' knowledge and attitudes related to halal food-based nutrition. Data analysis used the Wilcoxon test to test changes within groups, and the Mann-Whitney test to compare differences between groups. Results: showed that halal food-based nutrition education with motion graphic audiovisual media significantly increased knowledge (p=0.000) and improved attitudes (p=0.000) in adolescents. There is a significant difference in the use of motion graphic animation videos and video descriptions on knowledge (p=0.003) and there is no significant difference in the use of motion graphic animation videos and video descriptions on attitudes (p=0.554). Conclusion: There Significant improvements occurred in knowledge and attitudes through motion graphic and description audiovisual media. Motion graphic media is more effective in increasing knowledge, while effectiveness on attitude remains.